Panyard Science: A 2010 Melody - Barrow, Dorian (Daily Express, 2006)
This article suggests that a new teaching paradigm is urgently needed in science education in Trinidad and Tobago if established achievement targets are to be achieved. It suggests a paradigm of teaching that is embracing of more students, more student-centred, inquiry-based, and creative. It proffers the panyard method of education advocated by Lloyd Best, with its unique inclusive approach to teaching and learning, as a suitable model
Keywords: Science education; Child welfare; School Safety Zones; Trinidad and Tobago